Low serum vitamin D is associated with failure of Helicobacter pylori treatment - Salehi, Mohammad; Nikpour, Shahriar; Bagherian Khoozani, Narges (Student Research in Translational Medicine, 2021)
Background and aims: Helicobacter pylori are the most common gastrointestinal infection worldwide. Determination of contributing factors for successful eradication of Helicobacter pylori is important for better infection control. Therefore, this study was conducted to investigate the association between serum vitamin D deficiency and Helicobacter pylori eradication rate. Results: The results of this study demonstrated that before-treatment vitamin D level was between 10 and 20 ng/dL in majority of unsuccessful cases (40.4%) and it was more than 30 ng/dL in majority of successful cases (83.7%) showing statistically significant difference (P < 0.001). Conclusion: This study showed a significant association between vitamin D deficiency and Helicobacter pylori eradication and low vitamin D level resulted in failure of treatment; Hence in unsuccessful cases, assessment of vitamin D level and possible supplementation in those with hypovitaminosis D is recommended.